Comparison of Real-time RT-PCR cycle threshold (Ct) values with clinical features and severity of COVID-19 disease among hospitalized patients in the first and second waves of COVID-19 pandemic in Chennai, India - Sudhakar Natarajan; Mohan Ranganathan; P L Natarajan; Manohar Nesakumar; S Anbalagan; K Lucia Precilla; H Hemalatha; M Kannan; G Narendran; S Mahalakshmi; Gomathi Karmegam; Lakshmi Prakash; et al. (Journal of Clinical Virology Plus, 2023)
Introduction: Real-time reverse transcriptase-polymerase chain reaction (rRT-PCR) of nasopharyngeal/ oropharyngeal swab has been the gold standard test for detection of SARS-CoV-2 infection The relationship between cycle threshold (Ct) values of rRT-PCR and severity of disease remain disputable and not clearly defined in COVID-19. Methodology: This is a single-centered retrospective observational study conducted at Government Corona Hospital (GCH), Guindy, Chennai. In the present study, we compared the Ct value of rRT-PCR from nasopharyngeal swab specimens with a diverse range of symptoms and disease severity among 240 individuals who were hospitalized with COVID-19, viz., mild cases (MC; n = 160), moderately severe cases (MSC; n = 46) and severe cases (SC; n = 34) in the first and second waves of COVID-19 pandemic. Results: The study included 240 hospitalized COVID-19 patients with a median age of 52 years (range 21 to 90 years). MC, MSC, and SC all had median Ct values of 25.0 (interquartile range – IQR 20.0 to 30.5), 29.5 (IQR 23.0 to 34.0), and 29.0 (IQR 24 to 37.5) for the ORF1ab gene. The Ct value differed significantly between mild vs moderate, and mild vs severe cases. The Ct value of SC group with co-morbidity of type 2 diabetes have a significant difference compared to non-diabetes group (p value <0.05). There was a significant difference in the median Ct value of ORF1ab gene among the MSC group and MC but not in the SC group in the first and second waves of the pandemic (p<0.05). Conclusion: We conclude that SARS-CoV-2 Ct values of rRT-PCR alone does not have a role in aiding severity stratification among patients with COVID-19 since the viral dynamics and Ct value may vary due to the emerging variants that occur in different waves of the pandemic.